Desenho de rede de transporte público para Feira de Santana – Ba: uma aplicação do método RESET - Sodré, Bruno Fernandes Araújo (2020)
The cities offer several activities spread over their territory and for this reason, the urban mobility is essential for their functioning. The issue of transportation has always been at the center of discussions on local politics and is a frequent target of complaints from residents. This work presents an Illustrative Essay (EI, EnsaioIlustrativo in Portuguese) for a new design of the Public Transport Network of the Integrated Transport System (SIT, or Sistema Integrado de Transporte) in the municipality of Feira de Santana – Bahia, using the RESET Method. This method consists of identifying the urban centralities (or Development Poles, in portuguesePolos de Desenvolvimento) that must be directly interconnected by new structural lines of the SIT to promote the enhancement of urban activities and to decentralize the current public transport lines. The result identified that there are ten (10) Consolidated DPs and five (5) emerging in the city of Feira de Santana, which shows the need to redesign the SIT to directly interconnect the DPs in order to better meet the displacement needs of the population of the fair.